INTENTION AND ROLE OF ANTI-BULLYING CAMPAIGN OF FAMILY CHANNEL CANADA: A CRITICAL DISCOURSE ANALYSIS APPROACH - TALA S., OSSA BODHI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: CDA, anti-bullying campaign, government, Family Channel Canada, intention, role, viewers.Family Channel’s Anti-Bullying campaign is an unprofitable advertisement that is created by Family Channel Canada and Canadian government as the two biggest powerful sides in Canada. Although the campaign asks people to take astand against bullying, but it is well known ability to influence people and spreadinformation makes Family Channel Canada and Canadian government insert their own importance behind it. Then, CDA is a suitable approach to analyze it. The study is aimed: (1) to identify the intention behind creating Family Channel’s Anti-Bullying campaign; (2) to find out the role of Family Channel’s Anti-Bullying campaign for society; (3) to find out whether the viewers agree or disagree with Family Channel’s Anti-Bullying campaign.This study uses qualitative quantitative approach to provide better understanding and answer to wide range of research questions. The qualitativeresearch could provide in-depth and rich data, while the quantitative method isuseful toward generalizing research findings.This study reveals that behind the campaign, there is hidden intention to build good imagery of Canadian government and Family Channel Canada. This campaign’s role is to lead the society to the path that has been planned by theCanadian government and Family Channel Canada and to mold public’s opinion.Lastly, there are 143 agree comments from the total 509 comments, it could begeneralized that viewers actually agree with this campaign.The writer suggests the society to be more selective and smart in watchingsomething. The powerful sides also should maintain their power well and use itonly for the society needs. It would be better if the next researcher digs up deeper in the field of discourse in our daily life. Maybe, the discourse that lays behind some figures and images in advertisements. Developing the discourse behind those images could also do by combining the theory of CDA and theory of visual design.